2020
DOI: 10.1029/2020wr027949
|View full text |Cite
|
Sign up to set email alerts
|

Constraining Remote River Discharge Estimation Using Reach‐Scale Geomorphology

Abstract: Recent advances in remote sensing and the upcoming launch of the joint NASA/CNES/CSA/ UKSA Surface Water and Ocean Topography (SWOT) satellite point toward improved river discharge estimates in ungauged basins. Existing discharge methods rely on "prior river knowledge" to infer parameters not directly measured from space. Here, we show that discharge estimation is improved by classifying and parameterizing rivers based on their unique geomorphology and hydraulics. Using over 370,000 in situ hydraulic observati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 94 publications
(162 reference statements)
1
30
0
Order By: Relevance
“…and decile thresholding discharge estimation method developed by Mengen et al (2020) contribute to a significant improvement in discharge estimation. However, estimation accuracy of the aforementioned method using only satellite-observed cross-sectional width data is not always guaranteed if no previous estimates were made (Hagemann et al, 2017;Brinkerhoff et al, 2020).…”
Section: Accepted Articlementioning
confidence: 99%
See 1 more Smart Citation
“…and decile thresholding discharge estimation method developed by Mengen et al (2020) contribute to a significant improvement in discharge estimation. However, estimation accuracy of the aforementioned method using only satellite-observed cross-sectional width data is not always guaranteed if no previous estimates were made (Hagemann et al, 2017;Brinkerhoff et al, 2020).…”
Section: Accepted Articlementioning
confidence: 99%
“…Feng et al (2019) affirmed the possibility of estimating discharge independent of groundbased measurements with BAM. Recently, geo-BAM method proposed byBrinkerhoff et al (2020)…”
mentioning
confidence: 99%
“…Assimilation of future pre-SWOT data clearly corrected hydrological models on a global and continental scale, by reducing discharge errors from~30% to~24% [43]. The remote sensing-enabled hydrological simulation has been conducted across many basins [44,45]. Furthermore, revolutionary advances in machine learning methods have demonstrated great potential in streamflow prediction.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the current hydrodynamic module has not considered the regional parameterization which could also be important for flood performance. Studies have indicated that the use of identical parameters for the entire basin is problematic (e.g., Mateo et al., 2014; Yamazaki et al., 2011), which can be attributed to the unique geomorphology and hydraulics of the basin and its sub‐basins (Brinkerhoff et al., 2020). Accurate flood simulations thus require regional parameterization.…”
Section: Introductionmentioning
confidence: 99%